ABCs FOR A PEACEFUL ME : A Mindfulness Seek-and-Find Book - Becker, Shelly; Yaccarino, Dan, 1965- (New York : Abrams Appleseed, 2024)
A is for appreciate, B is for breathe, C is for connect, and D is to discover all of the great ways little ones can bring mindfulness into their daily routines. Featuring bold, colorful art, each spread focuses on a unique word promoting a healthy body-mind connection; a hidden object relating to the letter; and an animal, such as an antelope, a bear, an elephant, a tiger, and even a unicorn. Young readers will delight in learning this unique alphabet, as well as new ways to self-soothe and express themselves
On board pages.
Keywords: Mindfulness (Psychology) -- Juvenile literature; Calmness -- Children's picture books -- Juvenile literature; Self-actualization (Psychology) in children -- Children's picture books -- Juvenile literature; Picture books; Alphabet books; Picture books